Implementation Of The Linear Congruent Method In Interactive Quiz Games Application - Tonni Limbong; Zekson Arizona Matondang (INFOKUM, 2021)
The implementation of the Linear Congruent Method (LCM) in the interactive quiz game based on macromedia selects the suitcase used to generate random numbers. Generating numbers using the linear congruent method uses the formula x(n+1) = (axn+c) mod m. Giving variable values that continue to change greatly affects the game process and can avoid the occurrence of fixed or repeated patterns. In addition, giving a variable that changes can also prevent duplication of questions in a row. Meanwhile, to prevent unwanted random numbers from emitting is to set the variable m as a barrier. From the results of the implementation of the above method in an interactive quiz based on macromedia flash, it can display very varied suitcases that can be played by users with each level of difficulty.